Demand Spillovers and the Collapse of Trade in the Global Recession - Yi, Kei-Mu (IMF Working Papers; Working Paper, 2010)
This paper uses a global input-output framework to quantify US and EU demand spillovers and the elasticity of world trade to GDP during the global recession of 2008-2009. We find that 20-30 percent of the decline in the US and EU demand was borne by foreign countries, with NAFTA, Emerging Europe, and Asia hit hardest. Allowing demand to change in all countries simultaneously, our framework delivers an elasticity of world trade to GDP of nearly 3. Thus, demand alone can account for 70 percent of the trade collapse. Large changes in demand for durables play an important role in driving these results.